One-pot pyrolysis route to Fe−N-Doped carbon nanosheets with outstanding electrochemical performance as cathode materials for microbial fuel cell - Sun, Yong; Zhang, Zezhen; Sun, Yongming; Yang, Gaixiu (International Journal of Agricultural and Biological Engineering, 2020)
The naturally lackadaisical kinetics of oxygen reduction reaction (ORR) in the cathode is one of the important factors that restrict the development of air-cathode microbial fuel cells (MFCs). In this work, the iron-nitrogen-carbon hierarchically nanostructured materials had been successfully fabricated by pyrolyzing glucose, iron chloride, and dicyandiamide with the aim of solving the issue. The obtained catalyst with an ultrathin nanostructure demonstrated an idiosyncratic electrocatalytic activity caused by the high content introduction of nitrogen and iron atoms, large surface area, which will offer sufficient active sites for improving the charge/mass transfer and reducing the diffusion resistance. Furthermore, with the increase of N dopant in the catalyst, better ORR catalytic activity could be achieved. Illustrating the N doping was beneficial to the ORR process. The high content of N, BET surface area caused by the N increasing could be responsible for the superior performance according to results of X-Ray photoelectron spectroscopy (XPS), Raman and Brunner-Emmet-Teller (BET) analysis. The ORR on the Fe–N3/C material follows 4e− pathway, and MFCs equipped with Fe–N3/C catalyst achieved a maximum power density (MPD) of 912 mW/m2, which was 1.1 times of the MPD generated by the commercial Pt/C (830 mW/m2). This research not only provided a feasible way for the fabrication of Pt-free catalyst towards oxygen reduction but also proposed potential cathode catalysts for the development of MFCs.Keywords: one-pot pyrolysis route, Fe−N-Doped carbon nanosheets, microbial fuel cells, iron-nitrogen co-doping, carbon based catalyst, electrochemical performance, cathode materialsDOI: 10.25165/j.ijabe.20201306.5765Citation: Sun Y, Zhang Z Z, Sun Y M, Yang G X. One-pot pyrolysis route to Fe−N-Doped carbon nanosheets with outstanding electrochemical performance as cathode materials for microbial fuel cell. Int J Agric & Biol Eng, 2020; 13(6): 207–214.